Servicio militar y emigración. Reflexiones, posibilidades y problemas desde el caso español - Sarmiento, Érica; Gila, Oscar Álvarez (Confluenze. Rivista di Studi Iberoamericani, 2019)
Military service is one of the main reasons used both by contemporary witnesses and present-day historiography to explain mass migrations from Spain overseas in the 19th-20th centuries. In this article it is made a state of the art on the topic with the latest literature, as well as with a study on several primary sources. Even though there is a clear correlation between the figures of desertion and geographical distribution of emigration, it is still difficult to establish a direct causal link between them. Nonetheless, military recruitment is a very valuable source for studying overseas migration from a microlocal perspective.